The effect of incorrect foot placement on the accuracy of radiographic measurements of the hallux valgus and inter-metatarsal angles for treating hallux valgus - Erdil, M; Kuyucu, E; Ceylan, H. H; Sürücü, S; Erdil, I; Kara, A; Gülenç, B. G; Bülbül, M (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
PURPOSE OF THE STUDY Accurate radiographic measurements are crucial in treating hallux valgus (HV). This three-dimensional deformity should not be evaluated from one joint on one plane. However, in practice, surgeons measure the deformity only on transverse dorsoplantar radiographs. We determined the amount of error associated with positioning the foot incorrectly on radiographs. MATERIAL AND METHODS To simulate incorrect positions of the foot in radiographic evaluation, we designed an angled device that can move in transverse and frontal plane. In four patients with symptomatic HV, we took weight-bearing radiographs of the involved foot in seven different positions. These 28 radiographs were given identifying but meaningless labels. On each radiograph, six surgeons blinded to the position of the radiograph measured the HV angle (HVA) and the inter-metatarsal angle (IMA) and state the treatment plan according to five treatment options were given to participants. RESULTS Inter-observer agreement was high for measurements of HVA and IMA in all positions (interclass correlation coefficients, 0.96 and 0.88, respectively). However, intra-observer agreement was poor for HVA (intra-observer agreement, 0.17) but good for IMA (intra-observer agreement, 0.64). According to the measurements in different positions, intra-observer treatment choices revealed moderate results (ICC: 0.524). Clinical Relevance Radiographic measurements are very important on the treatment decisions of hallux valgus. The foot position can influence the measurement accuracy and can cause incorrect decisions. In this study, we evaluated the impact of foot positions on measurements of hallux valgus angle and inter-metatarsal angle. Additionally, we evaluated the incorrect foot positioning on treatment decisions. Moreover, we analyzed intra-observer and inter-observer agreements of these angles in various positions. CONCLUSIONS We recommend that measurements of IMA are more reliable than those of HVA for managing hallux valgus in terms of false weight bearing radiographs taken in different positions. Positional changes during foot radiographs could lead clinicians to perform incorrect HVA and IMA measurements. This could change the treatment option. HVA measurements were more affected with foot positioning. It is important to take full weight bearing foot radiographs in correct technique. Key words: hallux valgus, radiology, data accuracy.
Keywords: Patient Positioning; Foot; Reproducibility of Results; noha (od hlezna dolů); lidé; reprodukovatelnost výsledků; hallux valgus; Metatarsal Bones; radiografie; Radiography; polohování pacienta; metatarzální kosti; Hallux Valgus; Humans